A randomised controlled trial of an online menu planning intervention to improve childcare service adherence to dietary guidelines: a study protocol. Issue 9 (11th September 2017) - Yoong, Sze Lin; Grady, Alice; Wiggers, John; Flood, Victoria; Rissel, Chris; Finch, Meghan; Searles, Andrew; Salajan, David; O'Rourke, Ruby; Daly, Jaqueline; Gilham, Karen; Stacey, Fiona; et al.
Abstract : Introduction: The implementation of dietary guidelines in childcare settings is recommended to improve child public health nutrition. However, foods provided in childcare services are not consistent with guidelines. The primary aim of the trial is to assess the effectiveness of a web-based menu planning intervention in increasing the mean number of food groups on childcare service menus that comply with dietary guidelines regarding food provision to children in care. Methods and analysis: A parallel group randomised controlled trial will be undertaken with 54 childcare services that provide food to children within New South Wales, Australia. Services will be randomised to a 12-month intervention or usual care. The experimental group will receive access to a web-based menu planning and decision support tool and online resources. To support uptake of the web program, services will be provided with training and follow-up support. The primary outcome will be the number of food groups, out of 6 (vegetables, fruit, breads and cereals, meat, dairy and 'discretionary'), on the menu that meet dietary guidelines (Caring for Children) across a 1-week menu at 12-month follow-up, assessed via menu review by dietitians or nutritionists blinded to group allocation. A nested evaluation of child dietary intake in care and child body mass index will be undertaken in up to 35 randomly selected childcare services and up to 420 children aged approximately 3–6 years. Ethics and dissemination: Ethical approval has been provided by Hunter New England and University of Newcastle Human Research Ethics Committees. This research will provide high-quality evidence regarding the impact of a web-based menu planning intervention in facilitating the translation of dietary guidelines into childcare services. Trial findings will be disseminated widely through national and international peer-reviewed publications and conference presentations. Trial registration: Prospectively registered with Australian New Zealand Clinical Trial Registry (ANZCTR) ACTRN12616000974404.